Optimizing the Au particle doping size for enhanced photocatalytic disinfection under low-intensity visible light - Hwang,GB; Heo,KJ; Jee,W; Panariello,L; Piovesan,J; Cornwell,M; Collauto,A; Kafizas,A; Ali,S; Knapp,C; Macrobert,AJ; Gavriilidis,A; et al. (ACS Nano, 2025)
Here, we present the effect of 1.2–9.9 nm Au particles on crystal violet-treated polymer under a low intensity of visible light. The use of Au particles ≤ 6.3 nm promoted charge carrier transfer from crystal violet to Au particles. Photospectroscopy analyses and DFT computations revealed that a change in the electronic band structure caused by the size reduction of the particle altered the charge carrier transfer pathway in crystal violet. Especially for crystal violet1.2 nm Au particles, charge carrier transfer predominantly occurs at the S1 of crystal violet because the T1 state lacks sufficient potential energy for transfer. 1.2 nm Au particles on crystal violet not only most significantly enhanced the generation of O2•–, H2O2, and •OH by minimizing unnecessary side reactions or energy loss but also showed the most potent disinfection activity against Staphylococcus aureus, even at low visible light flux levels (0.037–0.054 mW cm–2), which resulted in a 5.3 log reduction in viable bacteria after 6 h exposure to visible light. This finding provides fundamental insights into the Au effect as a cocatalyst in photocatalysts and the development of light-activated self-sterilizing surfaces that can be applied to various hospital surfaces to prevent the spread of pathogens, which remains a global challenge.